PREFERENSI AGAMA DAN INKLUSI KEUANGAN ISLAM - Niswatun Hasanah (LPPM Institut Agama Islam Qomaruddin Gresik, 2023)
ABSTRACT The relationship between religious preference and financial inclusion in a number of countries around the world still raises questions. Whether religious preference can increase Islamic financial inclusion is the question that this paper seeks to answer. This article attempts to examine four articles on religious preference and Islamic financial inclusion. This research is a library research, using data in the form of books, articles, and the like. Data analysis used is the method of content analysis (content analysis). The content analysis method is used to determine the extent to which religious preferences increase Islamic financial inclusion. The results of the study show that on the one hand religiosity can affect financial inclusion in various states of the United States of America (US) and in various countries globally. However, higher levels of religiosity are negatively correlated with use of financial services across all levels of society. However, on the other hand, there is a significant relationship between one's level of religiosity and one's reasons for saving at an Islamic financial institution. In addition, Islamic financial inclusion is not only driven by religious factors, but also supported by technological sophistication, literacy, political commitment, regulations, and so on. In Indonesia, Islamic financial inclusion, which is still low, can be increased through optimizing the role of Islamic boarding schools with the kiai or ulema as the central figure. Keyword: Religious Preference, Inclusion, Islamic Finance ABSTRAK Hubungan preferensi agama dengan inklusi keuangan di sejumlah negara di dunia masih menimbulkan tanda tanya. Apakah prefensi agama dapat meningkatkan inklusi keuangan Islam adalah pertanyaan yang ingin dijawab dalam tulisan ini. Artikel ini mencoba menelaah empat artikel tentang preferensi agama dan inklusi keuangan Islam. Penelitian ini merupakan penelitian kepustakaan (library research), dengan menggunakan data berupa buku, artikel, dan sejenisnya. Analisis data yang digunakan adalah metode analisis isi (content analysis). Metode analisis isi digunakan untuk mengetahui sejauh mana preferensi agama dalam meningkatkan inklusi keuangan Islam. Hasil penelitian menujukkan bahwa di satu sisi religiusitas dapat memengaruhi inklusivitas keuangan di berbagai negara bagian Amerika Serikat (AS) dan di berbagai negara secara global. Akan tetapi, tingkat religiusitas yang lebih tinggi berkorelasi secara negatif dengan penggunaan layanan keuangan di seluruh lapisan masyarakat. Namun, di sisi lain terdapat hubungan signifikan antara tingkat religiusitas seseorang dan alasan seseorang menabung di lembaga keuangan syariah. Selain itu, inklusi keuangan Islam tidak hanya didorong oleh faktor agama, tetapi juga ditopang oleh kecanggihan teknologi, literasi, komitmen politik, regulasi, dan lain sebagainya. Di Indonesia, inklusi keuangan Islam yang masih rendah, dapat ditingkatkan melalui optimalisasi peranan pesantren dengan tokoh sentralnya kiai atau ulama. Kata kunci: Preferensi Agama, Inklusi, Keuangan Islam